Produção de grãos e outras características agronômicas de milho e feijão em dois sistemas de associação - Cardoso , Milton José; Nogueira Fontes , Luiz A; Domingos Galvão , José; Sediyama, Carlos S; Fernandes Lopes , Nei (Revista Ceres, 2025)
Yield and other characteristics of corn and bean (Phaseolus vulgaris L.) production systems were studied in a red-yellow dystrophic cambial Podsol, terrace phase, in Viçosa, Minas Gerais, Brazil.